Information technology worker as Services Specialist: thriving in the service economy. - Yeo, Wei Lin. (2011)
This research investigated information technology service management (ITSM) and its service specialists in Singapore. The agenda of this study included what the current state of ITSM was; how users rate ITSM specialists’ expertise and how successful ITSM is being roll out in the industry.